Psychological features of systemic sclerosis: results from an observational study - Sara Romanazzo; Caroline Rometsch; Alessia Marangoni; Serena Guiducci; Fiammetta Cosci; Fiammetta Cosci (Frontiers in Medicine)
Objectives(a) Assessing mental disorders, psychological distress, psychological wellbeing in patients with systemic sclerosis (SSc); (b) identifying psychological features independently contributing to the status of having the diagnosis of SSc.MethodsTwo hundred SSc outpatients were compared with 100 healthy subjects. Mental disorders were assessed via the Mini International Neuropsychiatric Interview (MINI). Self-reported rating scales were administered: Health Assessment Questionnaire Disability Index (HAQ-DI), Symptom Checklist-90-Revised (SCL-90-R), Psychological Well Being scales (PWB). General linear models allowed to verify which psychological feature would individually make unique contributions to overall status of having the diagnosis of SSc.ResultsMajor depressive episode/disorder, panic disorder were more prevalent among patients with SSc (p < 0.05); SCL-90-R somatization and depression were more severe (p < 0.05) in SSc; PWB personal growth, positive relationships with others, purposes in life were poorer (p < 0.05) in patients with SSc if compared to healthy controls. The final general linear model, accounting for 20.4% of variance, showed that having the diagnosis of SSc was associated to lower SCL-90-R paranoid ideation and poorer PWB relationships with others.ConclusionSSc showed to present psychological features in need of assessment since some of them individually made unique contributions to overall status of having the SSc diagnosis.